Qualification Of Vacant Urban Lands As Potential Green Spaces Used ForOptimising The Storm Drainage System Of Resistencia City (Argentina) - Julieta M Daciuk; Valeria Schneider (International Journal of Built Environment and Scientific Research, 2021)
The increasing rainfall issues related with current humid periods, as part of city of Resistencia’s climate in Argentina, impact and affect their population. This city has an inefficient storm drainage system, as a result of human intervention in the natural environment. Moreover, there is a wide range of vacant land that can offer and integrated green open spaces system that could relief and absorb the overflow of rainfall, while ensuring optimum solutions to face floods with less intervention, less environmental impact and low investment. The outcomes of this research have pointed out four key sectors suffering frequent flood and could be relief with green open spaces. This vacant land, are still available to be incorporated as absorbent areas that could also be design a flooding park, offering not only absorbent areas but also could be useful for leisure purposes, available for the community.